Penerapan Akuntansi Pada Pelaku UMKM Desa Jambu Kecamatan Kayen Kidul Kabupaten Kediri - Muyassaroh, Nur Arifatul; solikah, Mar’atus; Widiawati, Hestin Sri (Universitas Nusantara PGRI Kediri, 2021)
The purpose of the study was to determine and analyze the educational background, business scale, and age of the business on the application of accounting in MSMEs in Jambu Village because many MSME actors have difficulty applying accounting to their businesses. This study used a quantitative approach with 30 research subjects. The data collection techniques used were questionnaires and documentation. The data analysis technique used in the research is the multiple linear regression analysis method. The results of this study indicate that educational background and age of business partially affect the application of accounting, while the scale of business partially does not affect the application of accounting. And simultaneously educational background, business scale, and business age have a significant effect on the application of accounting. This research is in line with (Hariri, 2020) which states that educational background, business scale, and business age affect the application of accounting. While research conducted by (Purwaningsih, 2018) which states that educational background has no effect on the application of accounting Keywords: accounting application, education background, business scale, business age